2004
DOI: 10.1002/app.20253
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and lyotropic behavior of mesogen‐linked cellulose acetates

Abstract: Three aromatic (p-carboxyl phenyl) esters, 4-(benzoyloxy) benzoic acid, 4-(4Ј-methylbenzoyloxy) benzoic acid, and 4-(4Ј-chlorobenzoyloxy) benzoic acid, were synthesized and they showed nematic monotropic or thermotropic behavior. The mesogen-linked cellulose acetates were first prepared by the reaction of aromatic (p-carboxyl phenyl) esters with cellulose acetate through esterification in the presence of N,N-dicyclohexylcarbodiimide (DCC) and 4-dimethylaminopyridine (DMAP). Their degrees of mesogenic unit subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…MWCNTs‐OH (50 mg), PAA (200 mg), DCC (50 mg), DMAP (10 mg), and THF (50.0 mL) were heated at 65 °C in a flask while the reaction mixture was vigorously stirred under nitrogen protection for 48 h. The solid product, denoted as PAA‐ g ‐MWCNTs later, was collected and washed five times with anhydrous THF and finally was placed in dry nitrogen atmosphere 15, 16…”
Section: Methodsmentioning
confidence: 99%
“…MWCNTs‐OH (50 mg), PAA (200 mg), DCC (50 mg), DMAP (10 mg), and THF (50.0 mL) were heated at 65 °C in a flask while the reaction mixture was vigorously stirred under nitrogen protection for 48 h. The solid product, denoted as PAA‐ g ‐MWCNTs later, was collected and washed five times with anhydrous THF and finally was placed in dry nitrogen atmosphere 15, 16…”
Section: Methodsmentioning
confidence: 99%
“…The liquid crystalline behavior of cellulose derivatives has since aroused much interest in the field of liquidcrystalline polymers (Bhadani and Gray 1983;Isogai et al 1984;Pawlowski et al 1987;Yamagishi et al 1988;Chen et al 1992;Jiang and Huang 1993;Shaikh et al 1999;Huang et al 2007;Godinho et al 2009;Almeida et al 2009). During recent decades, several studies reported the introduction of the bulky and rigid mesogenic substituents on the cellulose backbone as side groups (Terbojevich et al 1999;Wu et al 2002Wu et al , 2003Wu et al , 2004Granström et al 2009). Although the chemical structure of these cellulose derivatives is similar to those of combined MCSCLCPs (Chen et al 1999;Cha et al 2001), unfortunately, rigid mesogenic side groups cannot form ordered structure themselves and just act as substituents on cellulose derivatives, as relatively short spacers between the cellulose backbone and the mesogenic side groups, so these polymers are merely main-chain liquid-crystalline polymers in nature.…”
Section: Introductionmentioning
confidence: 99%
“…During these reactions, the carboxylic acids are activated by a reagent, which leads to an intermediately formed highly reactive carboxylic acid derivative. The activation of carboxylic acids with p-toluenesulfonyl chloride (TosCl) (Heinze and Liebert 2001;Heinze et al 2003;Shimizu et al 1991;Tosh et al 2000;Xu et al 2011;Zheng et al 2015) and N,N 0 -dicyclohexylcarbodiimide in combination with 4-pyrrolidinopyridine or 4-dimethylaminopyridine (Fujisawa et al 2011;Samaranayake and Glasser 1993;Wang et al 2014;Wu et al 2004;Yue and Cowie 2002) are typical examples of this synthetic technique (Grabner et al 2002;Heinze et al 2018). Homogeneous esterification of cellulose was carried out via in situ activation with TosCl in DMAc/LiCl for the synthesis of 3-(hydroxyphenylphosphinyl)-prop-anoic acid esters of cellulose (Zheng et al 2015).…”
Section: Fundamental Aspectsmentioning
confidence: 99%